Analisis Strategi Pemasaran Dalam Memasarkan Produk Jasa Studi Kasus pada Rumah Sakit Karya Bhakti - Sujana, Sujana; Nurwandi, Mohd (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research has purposes in order that Kerya Bhakti Hospital will be able to know the situation of service competition of The Hospital at present and in the future, to know its strengths and weaknesses, and to know the accurate maeketing strategies. The research method used by the author is SWOT analysis, namely by mapping the Hospitalâs strenghts weaknesses, opportunities, and threats. The mapping was made in questionnaire directed towar some experts the Hospital has. Their answers were used in SWOT matrix, IFE matrix, EFE matrix and IE matrix. Based on available data, it can be obtained internal strategy factor: 2,808, whereas external strategy factor: 2,727. By combining total score at each matrix (IFE and EFE), Karya Bhakti Hospital in the state of stability/growth. The strategy at this state, that should be selected is conducting guidance. From the analysis result, it can be concluded that Karya Bhakti Hospital shoul utilize concentration strategy in care of horizontal integration by conducting addition or increase of service facilities and creating product the other hospitals do not have. Key words: SWOT analysis; Marketing strategy